2015
DOI: 10.1038/pr.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

High protein intake in neonatal period induces glomerular hypertrophy and sclerosis in adulthood in rats born with IUGR

Abstract: Background: Intrauterine growth restriction (IUGR) and postnatal nutrition are risk factors for cardiovascular and renal diseases in both humans and animals. The long-term renal effects of protein intake early in life remain unknown. The objective was to evaluate the effects of a neonatal feeding with high protein (HP) milk on renal functions and structure in IUGR male rats. Methods: Maternal gestational low protein diet was used to produce IUGR. At day 5, IUGR pups were gastrostomized in the "pup-in-the cup" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Personalized approaches to postnatal nutrition in these infants may be more efficient than a one size fits all strategy. Of note, postnatal overnutrition fol- lowing early intrauterine undernutrition (with/without extrauterine undernutrition) and growth restriction is a particularly deleterious growth pattern for later vascular, renal, and metabolic functions, as observed by our group and others in rats [2,3]. Interestingly, transient postnatal overfeeding during lactation in the absence of any prenatal nutritional alteration leads to hypertension, heart dysfunction, and metabolic disorders in adulthood [35,36].…”
Section: Nutritionsupporting
confidence: 64%
See 1 more Smart Citation
“…Personalized approaches to postnatal nutrition in these infants may be more efficient than a one size fits all strategy. Of note, postnatal overnutrition fol- lowing early intrauterine undernutrition (with/without extrauterine undernutrition) and growth restriction is a particularly deleterious growth pattern for later vascular, renal, and metabolic functions, as observed by our group and others in rats [2,3]. Interestingly, transient postnatal overfeeding during lactation in the absence of any prenatal nutritional alteration leads to hypertension, heart dysfunction, and metabolic disorders in adulthood [35,36].…”
Section: Nutritionsupporting
confidence: 64%
“…During this period, functional and regulatory capacities of systems and organs are set for the long term through an adaptation under the influence of clues received from the early, nutritional, stressing, and chemical environment, based on developmental plasticity and programming. Early translation patterns of the genome thus design life trajectories that condition the risk for later chronic diseases such as hypertension, obesity, type 2 diabetes, and other non-communicable diseases (NCDs) in adulthood, as shown by both epidemiological and animal studies [2]. During early development, environmental stimuli determine not only short-term but also lifelong and transgenerationally heritable effects due to epigenetic imprinting [3].…”
Section: Introductionmentioning
confidence: 99%
“…Rat models of IUGR induced by exposure to maternal LPD followed by early postnatal overnutrition during the lactation period or not according litter size reduction or increased protein intake to induce accelerated postnatal growth displayed alterations in renal structural development and a risk of chronic renal failure later in life. [165][166][167][168][169] Decreased glomerular number potentially leads to reduced filtration capacity, reduced salt and water retention and the subsequent development of HTN. Furthermore, early loss of nephron numbers/mass may result in a state of hyperfiltration in the remaining nephrons, which will lead to focal segmental glomerulosclerosis and further loss of glomeruli, thus initiating a vicious circle.…”
Section: Ckdmentioning
confidence: 99%
“…75,76 Boubred et al found in a male rat model of IUGR and hyperproteic postnatal feeding (13.1 g and 172 kcal v. 8.7 g and 155 kcal per 100 ml), that this condition was associated with proteinuria and glomerulosclerosis. 77 The same adverse outcomes were observed after overfeeding (by litter size reduction) alone, but not after IUGR alone. 78 In this study, early overfed animals with a normal BW had an increased number of nephrons, but decreased glomerular volume, suggesting an unchanged total glomerular filtration surface area.…”
Section: Animal Studiesmentioning
confidence: 76%